Kepemimpinan Publik Perempuan Dalam Perspektif Perbandingan Mazhab - Riyanto, Riyanto (Musawa Jurnal Studi Gender dan Islam, 2004)
Functionally speaking, judges and heads of the states are the two most strategic positions. The policies issued by those bureaucrats are very influential for the society. Therefore, these kinds of professions require significant responsibilities and certain qualifications. At this point, the capability of women to hold those positions is questioned. Generally speaking, almost all classical ulama maintained that women are not allowed to be judges, let alone to be the heads of a state. The reason given for this prohibition is that women are biologically seen as unable to perform such a task. However, contemporary ulama emphasized more on the capability of human being, be they men or women, to hold such a position. Moreover, these ulama applied a contextual approach in reading the Islamic texts.